REKAYASA GENETIKA DALAM PERSPEKTIF ISLAM (Kontroversi Kloning Terhadap Manusia) (Mazahib, 2007)
The development of gene technology has created some problems insofar as ethical questions are concerned. One form of the advancement of gene technology is human cloning which leads to harsh polemic between the proponents and the opponents. Both parties claim that their arguments are sound because they have carefully considered many aspects. How Islam views this human cloning issue will be discussed by this article. It argues that Islam’s position on this issue will be contingent upon how far moral is taken into account in determining the legal status of human cloning.